Oyster Mushroom Cultivation Training as Empowerment Program for Students of Foundation of Islamic Education and Social “Ar-Rohmah” - Rufiani Nadzirah; Dyah Ayu Savitri; Noer Novijanto (LP2M Universitas Jember, 2022)
Oyster mushroom is one of the horticultural commodities in Indonesia. This community empowerment program through oyster mushroom cultivation is designed as an effort to provide a sense of equality, partnership, and togetherness for the improvement of the community's economy. Islamic and Social Education Foundation